2013
DOI: 10.1128/aem.01566-13
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Electron Transfer to Fe(III) Oxides by the Hyperthermophilic Archaeon Geoglobus ahangari via a Direct Contact Mechanism

Abstract: The microbial reduction of Fe(III) plays an important role in the geochemistry of hydrothermal systems, yet it is poorly understood at the mechanistic level. Here we show that the obligate Fe(III)-reducing archaeon Geoglobus ahangari uses a direct-contact mechanism for the reduction of Fe(III) oxides to magnetite at 85°C. Alleviating the need to directly contact the mineral with the addition of a chelator or the electron shuttle anthraquinone-2,6-disulfonate (AQDS) stimulated Fe(III) reduction. In contrast, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 50 publications
0
56
0
Order By: Relevance
“…1B), are more likely to serve for adhesion than for twitching motility. The production of two distinct types of filaments, flagella and curled pilus-like thin appendages, was also reported for G. ahangari (27). Interestingly, cells simultaneously producing both flagellum-and pilus-like structures have not been identified in G. acetivorans cultures, suggesting that these processes are strictly regulated in the organism.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…1B), are more likely to serve for adhesion than for twitching motility. The production of two distinct types of filaments, flagella and curled pilus-like thin appendages, was also reported for G. ahangari (27). Interestingly, cells simultaneously producing both flagellum-and pilus-like structures have not been identified in G. acetivorans cultures, suggesting that these processes are strictly regulated in the organism.…”
Section: Resultsmentioning
confidence: 78%
“…Aciduliprofundum boonei" are also available; however, there are no published data on the genomic determinants of Fe(III) reduction in these organisms (26). It was recently shown that the obligate Fe(III)-reducing hyperthermophilic archaeon Geoglobus ahangari uses a direct-contact mechanism for the reduction of Fe(III) oxides to magnetite (27), but genomic determinants of these processes are unknown.…”
Section: G Eoglobus Acetivorans Sbh6mentioning
confidence: 99%
“…Direct contact with Fe(III) oxides and reliance on electron-shuttling or chelating compounds for reduction of Fe(III) are traits seen in both bacterial and archaeal species (1,(11)(12)(13)(14)(15)(16)61). In fact, the majority of electron transport proteins that transcriptomic and proteomic studies showed to be important for reduction of insoluble Fe(III) oxide by F. placidus have homologues in mesophilic Fe(III)-reducing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of c-type cytochrome proteins in Fe(III) reduction also seems to vary among hyperthermophilic archaea. While c-type cytochrome proteins appear to be involved in electron transfer to Fe(III) by G. ahangari (14), they are not required for Fe(III) respiration by Pyrobaculum species (13,16). In this study, Fe(III) respiration was examined in Ferroglobus placidus, a hyperthermophilic archaeon that was isolated from hydrocarbon-and iron-rich sediments associated with a hydrothermal system in Vulcano Island (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation